Good Fish Handling Techniques to Maintain the Quality of Catch from Ship to Consumer - Wijaya, Haryadi; Dien, Henny Adeleida; Tumbol, Reiny A.; Mentang, Feny (Sam Ratulangi University, 2024)
Proper handling of fish or fishery products from ships to consumers necessitates collaboration among fishermen, government agencies, and other stakeholders. By adopting a holistic approach encompassing technical, regulatory, and educational aspects, we can ensure the efficient and sustainable operation of fisheries supply chains for all involved parties. This article presented a literature review on good fish handling practices from ship to consumer, focusing on onboard handling, auctions, landing, and transportation. Using the search term 'Good Handling Practices for Fishing Products,' six articles out of 4,470 were identified that met the criteria for further discussion. The literature review findings highlighted optimal strategies for increasing fishing, auction, and transportation processes. These included improving record-keeping and documentation, implementing aerator systems to preserve fish quality, bulk fish cooling using ice cubes without water to mitigate quality deterioration, ensuring sanitation of fish distribution support equipment to prevent bacterial contamination, and utilizing tools such as Trolley Lifters to increase the efficiency of the fish distribution process. Therefore, governmental and non-governmental institutions should provide support and training to fishermen to maximize both the quality and quantity of fish catches. Keywords: Fish Handling Techniques, Catch Quality, Ships, Consumers